Evaluation of coeliac disease serological markers - Mustafa Kamil, leen K. (Journal of the Faculty of Medicine Baghdad, 2015)
Background: celiac disease, is an autoimmune inflammatory disease of the small intestine that is precipitated by the ingestion of gluten, a component of wheat protein, in genetically susceptible persons. Serologic tests for antibodies against Endomysium, Reticulin, and Gliadin identify most patients with the disease. Early diagnosis and management are important to forestall serious consequences of malabsorption, such as osteoporosis and anemia Aims of the study: This study compared the sensitivity, specificity, and predictive value of, anti-reticulin and anti-gliadin antibodies according to anti endomysium antibodies , in consecutive patients investigated for celiac disease antibodies. Patient& Methods: Total 509 patients (236 males&273 females) celiac disease patients who were referred to the immunology department in Teaching labs from January till December 2012 for serological detection of auto antibodies . Anti- Gliadin (IgG &IgA ) were measured by Enzyme Linked Immunosorbent Assay. whereas Anti-Endomyseal IgA & Anti-Reticulin IgA were detected by Indirect immunofluorescent technique on monkey oesophagus & kidney tissue respectively. Results: Most the cases for celiac disease were reported in the age group (1-10)years as antibodies against Gliadin (IgG,IgA) ,Anti-Endomesial IgA antibodies and anti-Reticulin IgA were detected in 130(66.7%),127(65.8%),39(79.6%) and 49(68.1%) respectively. Both anti-Gliadin IgA and anti Reticulin were detected significantly in females p values( 0.047, 0.008) respectively. The study showed that anti-Gliadin IgA is the most sensitive according to anti Endomyseal IgA and anti Reticulin was the most specific for screening of celiac disease. ; While Receiver Operating Characteristic (ROC) curve showed that anti gliadin IgA had the best sensitivity and specificity according to anti Endomysium test results. Conclusion: Predictive performance of the serological celiac disease tests showed that anti Gliadin IgA had the best sensitivity &specificity according to traditional anti Endomysium antibody test results.